THE EFFECTIVENESS OF USING GAMES IN TEACHING ENGLISH TO YOUNG LEARNERS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article investigates the effectiveness of using games as a teaching tool in English language instruction for young learners. In recent years, game-based learning has gained significant attention as an alternative to traditional teacher-centered approaches. The study explores how games influence young learners’ motivation, vocabulary acquisition, speaking skills, and overall engagement in the classroom. Using a qualitative and descriptive research approach, data were analyzed from existing studies, classroom observations, and educational research conducted over the past decade. The findings indicate that games create a low-anxiety learning environment, enhance learners’ participation, and promote meaningful language use. The results confirm that incorporating games into English language teaching significantly improves learning outcomes for young learners compared to traditional instructional methods.